2017
DOI: 10.3389/fmicb.2017.02420
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antioxidant Activities of Novel Actinobacteria Strain Isolated from Gulf of Khambhat, Gujarat

Abstract: Bacterial secondary metabolites possess a wide range of biologically active compounds including antibacterial and antioxidants. In this study, a Gram-positive novel marine Actinobacteria was isolated from sea sediment which showed 84% 16S rRNA gene sequence (KT588655) similarity with Streptomyces variabilis (EU841661) and designated as Streptomyces variabilis RD-5. The genus Streptomyces is considered as a promising source of bioactive secondary metabolites. The isolated novel bacterial strain was characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 69 publications
3
42
0
1
Order By: Relevance
“…S-2, aside from antibiotic activity, might display antitumor, anti-inflammatory, or antioxidant activities, or function as insecticides. Such activities have been previously reported in the Streptomyces genus [2,10,[70][71][72]. Considering the biosynthetic potential of the S-2 strain, future research focusing on investigation of these activities is ensured.…”
Section: Discussionsupporting
confidence: 58%
“…S-2, aside from antibiotic activity, might display antitumor, anti-inflammatory, or antioxidant activities, or function as insecticides. Such activities have been previously reported in the Streptomyces genus [2,10,[70][71][72]. Considering the biosynthetic potential of the S-2 strain, future research focusing on investigation of these activities is ensured.…”
Section: Discussionsupporting
confidence: 58%
“…As a result, marine microorganisms developed unique metabolic and physiological ability to survive by activating their environment adaptation genes (ENAs) (Almeida et al, 2019). Because of this, they produce different secondary metabolites that their terrestrial counterparts do not have (Imada, 2005;Zheng et al, 2011;Dholakiya et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25] Studies have shown that extracts of actinobacteria isolate from soil or marine sediments possess strong antibacterial and antioxidant activities. [26][27][28] Based on this, we investigated the antioxidant properties of the extract and the VLC fractions. The extract and VLC fractions showed high antioxidant activity in the DPPH assay, evident in the low IC 50 values obtained (1.008 -7.140 mg/mL) ( Table 4).…”
Section: Discussionmentioning
confidence: 99%